Performance Comparison of HS-TCP and TCP in Hierarchical Mobile IPv6 Network - Hayati, Nur; Putra, Mahesa Adhitya (Universitas Muhammadiyah Yogyakarta, 2017)
Technology information has been growing rapidly in the last few years. HMIPv6 is one of environment used in mobility internet connection. One of transmission used in this method is Transmission Control Protocol (TCP). TCP has a normal connection that connect mobile node to the internet and has a normal speed of transmission. This paper tries to compare TCP with another protocol. High Speed Transmission Control Protocol (HS-TCP) is a transport protocol that introduces new method by improving general algorithm of TCP in reducing time of loss recovery. HS- TCP is compared with TCÂ¬P to see the performance of each protocol. The simulation of these protocols is using Network Simulator 2.31 (NS-2.31). The topology of HMIPv6 concludes 1 Home Agent (HA), 2 Foreign Agent (FA), 1 Mobile Node (MN), 1 Correspondent Node (CN). The performance measurement is processed when MN moved from FA2 to FA1 while communicating with CN. Throughput of HMIPv6 will become the parameters for QoS. The result of the simulation shows that HS-TCP has a better performance than TCP by looking at the throughput which ran on the HMIPv6 topology. This simulation have proved that HS-TCP are suitable to be implemented in neighborhood supporting high speed. With bandwidth at 100 Mbps, we can see that HS- TCP is 32% better than HS-TCP, in 500 Mbps HS-TCP is better at 96% than TCP. In 1Gbps, HS-TCP is better at 85% than TCP and in 10Gbps, HS-TCP is better at 86% than TCP.Â